Competency Certification for Lifelong Learning and Professional Development in Technical Education: A Systematic Literature Review - Sri Anggreni; Mukhlisin Mukhlisin; Luis Miguel Oliveira de Barros Cardoso (Journal of Vocational, Informatics and Computer Education, 2026)
Purpose – This study aims to explore and map the utilization of competency certification, including micro-credentials, as a mechanism to support lifelong learning and professional development in response to the rapidly changing world of work. It focuses on understanding how certification contributes to skills validation, employability, and career mobility in educational and workplace contexts.Methods – This study adopts a Systematic Literature Review (SLR) approach guided by the PRISMA 2020 framework. Articles were retrieved from the Scopus database (2020–2025), yielding 363 records, of which 36 studies fulfilled the predefined inclusion criteria. The methodological quality and risk of bias were assessed using the Mixed Methods Appraisal Tool (MMAT) through independent evaluation by three reviewers. The findings were systematically synthesized to identify key patterns, thematic relationships, and research gaps regarding competency certification in the context of lifelong learning and professional development.Findings – The analysis reveals that competency certification plays a significant role in supporting lifelong learning by enabling the flexible, modular, and verifiable recognition of skills. Its effectiveness is shaped by factors such as competency-based design, alignment with labor market needs, institutional readiness, and the ability to ensure verification, portability, and interoperability of the acquired competencies. Furthermore, the integration of digital technologies, such as blockchain-based credentialing, digital badge infrastructures, and AI-supported assessment systems, enhances the transparency, scalability, and cross-platform recognition of credentials, transforming certification into a dynamic learning ecosystem.Research implications – This study highlights the importance of integrating competency certification into education and workforce development systems. This suggests that stakeholders, including educational institutions, industry, and policymakers, should collaborate to ensure interoperability, standardization, and alignment with evolving labor market demands. Such integration is essential for strengthening lifelong learning ecosystems and workforce adaptability.Originality – This study conceptualizes competency certification as a socio-technical system that integrates educational practices, institutional frameworks, and digital infrastructures. It emphasizes that certification is not merely a validation tool but a technology-enabled mechanism that supports continuous learning, professional development, and adaptive workforce readiness.